Analysis of quasistatic viscoelastic viscoplastic piezoelectric contact problem with friction and adhesion - CHOUGUI, Nadhir (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper we study the process of bilateral contact with adhesion and friction between a piezoelectric body and an insulator obstacle, the so-called foundation. The material’s behavior is assumed to be electro-viscoelastic- viscoplastic; the process is quasistatic, the contact is modeled by a general non-local friction law with adhesion. The adhesion process is modeled by a bonding field on the contact surface. We derive a variational formulation for the problem and then, under a smallness assumption on the coefficient of friction, we prove the existence of a unique weak solution to the model. The proofs are based on a general results on elliptic variational inequalities and fixed point arguments. Mathematics Subject Classification (2010): 74M10, 74M15, 74F05, 74R05, 74C10. Received 13 December 2019; Accepted 17 January 2020.